COMPARATIVE MODELLING PROTEIN VAKSIN NA BTB H5N1 MENGGUNAKAN SWISS MODEL - Amelia, Fitri; Iryani, Iryani (Sainstek : Jurnal Sains dan Teknologi, 2012)
Vaccine sequence of Neuraminidase BTB from previous research was studied by using swiss model server. Protein template was gotten from RSCB database by comparing the vaccine sequence with PDB database. HTY protein was used as a template for this vaccine. Template had 0.00e-1 E value, and 97% identity. The protein vaccine that has been modelled by swiss model had  good quality as immune inducer. Base on ramachandran plot analysis, protein model 1, 2, and 3 have amino acid residues in favoured region higher than 70%. They are 82,0% and 78,2%. Model 1 has the lowest non glysine amino acid residues in disallowed region area, that is 0%.   3D Structure of vaccine had 2086  hits of similarity with database on NCBI Key words: comparing modelling, H5N1 vaccine, swiss model